MONEY POLITIC DALAM PEMILU LEGISLATIF TAHUN 2024 PERSPEKTIF HUKUM ISLAM STUDI KASUS DI DESA TULUNGREJO KECAMATAN PARE KABUPATEN KEDIRI - Adinda Nurul Habibah; Awal Mukmin (Institut Agama Islam Hasanuddin Pare, 2025)
Money politics is an effort to gain support and votes by giving money, goods, or promises of office to voters during elections. This practice of money politics is prohibited by Law No. 7 of 2017 and in Islamic law, it is absolutely forbidden because it is similar to bribery. This research attempted to examine in more depth the factors causing the involvement of Tulungrejo village residents in money politics and how the law on money politics carried out by the Tulungrejo community is based on the perspective of Islamic law. This study uses a qualitative approach (field research), namely by obtaining primary data sources from several campaign teams and recipients of money involved in money politics in Tulungrejo Village, Pare District, Kediri Regency and secondary data from several literature studies on money politics, then data collection is carried out using methods in the form of interviews, observations, and documentation. The results of the research conducted, the author concluded several factors that cause the people of Tulungrejo Village to be involved in money politics, including the pragmatic mindset of the community, economic factors, educational factors, environmental factors, and legal factors. Money politics, according to the majority of scholars, is haram. The existence of rules is permitted because there is a specialization. And this specialization applies to someone who is in a state of emergency. The conditions for emergency are that the emergency has already occurred, not future, is the only way ordered by sharia, is carried out according to the level of not excessive, in a state of emergency it is obligatory to avoid something that causes more negativity, it is not permissible to immediately carry out actions that are not included in rukhsoh. Referring to the several factors above, the practice of money politics that occurs in Tulungrejo Village is included in the category of forbidden.